Anti-angiogenic treatment of endometriosis via anti-VEGFA siRNA delivery by means of peptide-based carrier in a rat subcutaneous model. Issue 8 (December 2018) - Egorova, Anna; Petrosyan, Mariya; Maretina, Marianna; Balashova, Natalia; Polyanskih, Lyudmila; Baranov, Vladislav; Kiselev, Anton
Abstract Development of gene therapy for endometriosis requires inhibition of vascularization in endometrial lesions. We have previously developed CXCR4 receptor-targeted siRNA carrier L1 and observed efficient RNAi-mediated down-regulation of VEGFA gene expression in endothelial cells followed by decrease in VEGFA protein production and inhibition of cell migration. In this study we evaluated L1 carrier as non-viral vector for anti-VEGFA siRNA delivery into endometrial implants in rat subcutaneous endometriosis model created by subcutaneous auto-transplantation of uterus horn's fragments. Therapeutic anti-angiogenic efficiency of anti-VEGFA siRNA/L1 polyplexes was evaluated by lesion size measurement, histopathologic examination, immunohistochemical staining and real-time reverse transcriptase-PCR analysis. After in vivo administration of anti-VEGFA siRNA we observed a 55–60% inhibition of endometriotic lesions growth and approximately two-fold decrease in VEGFA gene expression in comparison with untreated implants. Results of immunohistochemical examination of endometriotic lesions confirmed anti-angiogenic effects of anti-VEGFA siRNA/L1 polyplexes. Ultimately, our results demonstrate the efficiency of anti-angiogenic treatment of EM by means of anti-VEGFA siRNA delivery with L1 peptide-based carrier.